Packing material, its manufacturing method, and size exclusion chromatography column
By introducing specified long-resistance copolymers into the cross-chain polymer filler and combining through ethanol bonds to form high-alkali resistant filler, the sensitivity and non-specific adsorption of fillers to the alkaline environment in the prior art is solved, and efficient protein purification and industrial-scale production are achieved.
Patent Information
- Application Number
- JP2023531731
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-06-29
- Filing Date
- 2022-06-03
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2042-06-03
AI Technical Summary
The prior art lacks fillers with high alkali resistance, making it difficult to effectively prevent non-specific adsorption and clean recovery during protein purification.
A filler formed by copolymerizing a specified length-resistance copolymer with a transchain polymer, which binds to the end-hydroxyl groups of the transchain polymer through an ethanol bond to form a high alkali-resistant filler.
The production of high alkali-resistant fillers is achieved, the efficiency and yield of the protein purification process is improved, and the production and application on an industrial scale is simplified.
Smart Images

Figure 0007666599000001 
Figure 0007666599000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a packing material for size exclusion chromatography for protein purification, and more particularly to a packing material having high alkali resistance. [Background technology]
[0002] Size exclusion chromatography, which separates molecules in order of molecular size, is widely used to separate water-soluble polymers such as polysaccharides, peptides, proteins, DNA, and RNA. Size exclusion chromatography has the advantage that biopolymers such as proteins can be treated under mild conditions, allowing the separation and fractionation of biopolymers with minimal denaturation. The separated and fractionated biopolymers are used in biochemical reactions and industrial applications in the food, pharmaceutical, and chemical industries, and the market has expanded and grown significantly in recent years.
[0003] To meet this demand, there is a need for separation and preparative packing materials that can be used in large quantities on an industrial scale. In particular, in the field of gene therapy drugs, where future market expansion is expected, there is a need for further improvements in the functionality of packing materials in order to significantly improve the productivity of purification processes for viral vectors and virus-like particles. In particular, there is a need for packing materials that can be used for precise separation and purification of viral vectors and virus-like particles with large molecular sizes, and that can easily perform precise size separation throughout the entire process from culture to purification.
[0004] For this reason, packing materials are required to have different challenges and requirements from analytical columns: good separation efficiency, which allows the separated products to be recovered; the ability to suppress non-specific adsorption even when they contain a variety of components, such as impurities and unknown components contained in biopharmaceuticals derived from fermentation products; and the ability to be washed and regenerated with strong alkali.
[0005] However, a filler having such alkali resistance has not yet been proposed.
[0006] The present applicant has proposed a packing material for size exclusion chromatography using a methacrylate monomer in International Publication No. 2018 / 155241 (Patent Document 1). Patent Document 1 discloses a packing material that has undergone a process in which a monomer having a glycidyl group and a crosslinking agent are polymerized in the presence of a polymerization initiator, porous particles made of the resulting copolymer are hydrophilized with a sugar alcohol, and then the remaining glycidyl groups are ring-opened with a mineral acid; however, there is a demand for a packing material with higher alkali resistance.
[0007] In addition, Japanese Patent No. 5315691 (Patent Document 2) discloses a filler in which the surface of crosslinked polymer particles is hydrophilized using a monomer having a special structure among methacryloyl monomers with improved resistance to alkaline aqueous solutions. The monomer used in Patent Document 2 is not a general-purpose monomer, so it is difficult to obtain easily and there is a problem in that the cost is high. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] International Publication No. 2018 / 155241 [Patent Document 2] Patent No. 5315691 Summary of the Invention [Problem to be solved by the invention]
[0009] Although there are various reports as described above, there is still a need for a packing material that is highly alkaline resistant and suitable for preparative separation.
[0010] The present invention aims to solve the above-mentioned problems, and more specifically, to provide a packing material for size exclusion chromatography having high alkali resistance and a method for producing the same. [Means for solving the problem]
[0011] As a result of intensive research aimed at solving the above problems, the present inventors have found that a filler in which a specific block copolymer is introduced into porous particles made of a crosslinked copolymer of a monomer having a glycidyl group and a crosslinking agent has high alkali resistance, and have thus completed the present invention. [1] A filler comprising a porous organic polymer support containing 60 to 95 mol % of repeating units derived from glycidyl methacrylate and 5 to 40 mol % of repeating units derived from a polyfunctional monomer, and one end of a block copolymer represented by the following formula 1 bonded via an ether bond derived from a terminal hydroxyl group. (Formula 1) HO-(C 2 H 4 O) l -(C 3 H 6 O) m -(C 2 H 4 O) n -H (In formula 1, l is an integer from 5 to 140, m is an integer from 15 to 75, and n is an integer from 5 to 140. The proportion of m in the total of l, m, and n is 5 to 85%.) [2] The filler according to [1], wherein the sum of l, m, and n of the block copolymer is 30 to 330. [3] The filler according to [1] or [2], wherein the polyfunctional monomer is a (meth)acryloyl-based monomer containing two or more (meth)acryloyl groups. [4] The filler according to any one of [1] to [3], wherein the polyfunctional monomer is either ethylene glycol dimethacrylate or glycerin-1,3-dimethacrylate. [5] The packing material according to any one of [1] to [4], which has an exclusion limit molecular weight of 1,000,000 or more. [6] A method for producing the filler according to any one of [1] to [5], A step of polymerizing raw material monomers including glycidyl methacrylate and a polyfunctional monomer in the presence of a diluent and a polymerization initiator to obtain a porous organic polymer carrier α, A step (A) of adjusting the concentration of the polyfunctional monomer in the raw material monomer to 5 mol % to 40 mol % and using the diluent in an amount of 0.8 to 4.0 times the total volume of the raw material monomer; and (B) ring-opening the glycidyl group derived from glycidyl methacrylate of the porous organic polymer carrier α with a block copolymer represented by formula 1 to obtain a filler β in which one end of the block copolymer represented by formula 1 is bonded to the porous organic polymer carrier α via an ether bond derived from a terminal hydroxyl group. (Formula 1) HO-(C 2 H 4 O) l -(C 3 H 6 O) m -(C 2 H 4 O) n -H (In formula 1, l is an integer from 5 to 140, m is an integer from 15 to 75, and n is an integer from 5 to 140. The proportion of m in the total of l, m, and n is 5 to 85%.) [7] A size-exclusion chromatography column, in which the packing material according to any one of [1] to [5] is packed in a liquid chromatography case. Effect of the Invention
[0012] According to the present invention, a packing material having high alkali resistance and excellent separation efficiency can be obtained. This enables the speed of separation processing to be increased. Furthermore, the packing material can be produced using inexpensive raw materials and a simple process, and is easily applicable to industrial scale use of a large amount of packing material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The following describes in detail the embodiments of the present invention. However, the materials, dimensions, etc. exemplified in the following description are merely examples, and the present embodiment is not limited thereto. Appropriate modifications can be made within the scope that does not change the gist of the present invention.
[0014] The filler includes not only those that can be used as fillers by themselves, but also those that can be used after their surfaces are modified according to the purpose.
[0015] In this specification, "(meth)acrylic" means acrylic and methacrylic, and the same applies to "(meth)acryloyl". [Filler] The packing material of the present embodiment has a structure in which a specific skeleton is bonded to a porous organic polymer carrier α as shown below. (Porous organic polymer carrier α) The porous organic polymer carrier α is composed of a copolymer containing 60 to 95 mol% of repeating units derived from glycidyl methacrylate and 5 to 40 mol% of repeating units derived from a polyfunctional monomer. Preferably, it contains 65 to 95 mol% of repeating units derived from glycidyl methacrylate and 5 to 35 mol% of repeating units derived from a polyfunctional monomer, more preferably 75 to 92 mol% of repeating units derived from glycidyl methacrylate and 8 to 25 mol% of repeating units derived from a polyfunctional monomer. When the ratio of repeating units fused from a polyfunctional monomer is low, the final packing may be unsuitable for use due to high back pressure, and when the ratio of repeating units fused from a polyfunctional monomer is high, non-specific adsorption may occur, making it impossible to separate as desired. It is possible to obtain the porous organic polymer carrier of this embodiment even if glycidyl acrylate is used.
[0016] The polyfunctional monomer is a compound having two or more ethylenic double bonds in the molecule. As the polyfunctional monomer, one having two or more (meth)acryloyl groups in the molecule is preferable. Specifically, alkanediol di(meth)acrylate (the number of carbon atoms of the alkane is 1 to 12), trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, pentaerythritol penta(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, etc. can be mentioned, and other examples include polyfunctional urethane (meth)acrylate, etc. These compounds may be used alone or in combination of two or more.
[0017] Preferably, at least one of ethylene glycol dimethacrylate and glycerin-1,3-dimethacrylate is contained. Ethylene glycol dimethacrylate and glycerin-1,3-dimethacrylate may account for 50 mol% or more of the total amount of polyfunctional monomers, and preferably 80 mol% or more. Since this allows the formation of pores suitable for separation, it is most preferable that the total amount is ethylene glycol dimethacrylate and / or glycerin-1,3-dimethacrylate.
[0018] The copolymer may contain other monomer units as long as the total amount of the glycidyl methacrylate and polyfunctional monomer is 95 mol % or more as monomer units, so long as the properties of the porous particles are not significantly changed. As the other monomers, monomers having a glycidyl group, such as 3,4-epoxycyclohexylmethyl methacrylate, 4-hydroxybutyl acrylate glycidyl ether, methyl (meth)acrylate, ethyl (meth)acrylate, etc. can be used.
[0019] The degree of crosslinking of the copolymer is 5 mol % to 40 mol %, preferably 5 mol % to 35 mol %, and more preferably 8 to 25 mol %.
[0020] The degree of crosslinking is (Total molar number of polyfunctional monomers / Total molar number of all monomers) × 100 = Crosslinking degree (mol%) It is represented by
[0021] When the crosslinking degree is low, the final filler may have a high back pressure in the column for size exclusion chromatography and may not be suitable for use. When the crosslinking degree is high, non-specific adsorption may occur and the desired fractionation may not be possible. (Surface structure) In the present embodiment, the block copolymer represented by the following formula 1 is bonded to the porous organic polymer carrier α via an ether bond derived from a terminal hydroxyl group. That is, it is bonded via an ether bond generated by the reaction between the glycidyl group derived from glycidyl methacrylate in the copolymer constituting the carrier and the terminal hydroxyl group of the block copolymer. (Formula 1) HO-(C 2 H 4 O) l -(C 3 H 6 O) m -(C 2 H 4 O) n -H In formula 1, l is an integer from 5 to 140, m is an integer from 15 to 75, and n is an integer from 5 to 140. The proportion of m in the total of l, m, and n is 5 to 85%. l and n may be the same integer or different integers, and l > n or l < n may be possible. l is preferably an integer from 6 to 135, m is preferably an integer from 16 to 70, and n is preferably an integer from 6 to 135.
[0022] (C 3 H 6 O) The C3 alkyl group constituting it may be either n-propyl or isopropyl, but isopropyl is preferred to enhance hydrophobicity.
[0023] That is, on the carrier surface, (C 2 H 4 O) l or (C 2 H 4 O) nA highly hydrophilic block portion derived from (C 3 H 8 O) m A highly hydrophobic block portion derived from (C 2 H 4 O) l or (C 2 H 4 O) n The hydrophilic block portion originates from the side that is not bound to the carrier. By adopting this type of structure, non-specific adsorption is suppressed, and a packing material with high alkali resistance can be obtained.
[0024] The ratio of m to the total of l, m, and n in the block copolymer is 5 to 85%, preferably 10 to 75%, and more preferably 15 to 65%. Within this range, a packing material having particularly high alkali resistance and suppressed nonspecific adsorption can be obtained.
[0025] The sum of l, m, and n of the block copolymer is preferably 30 to 330, and more preferably 35 to 200. Within this range, a packing material having particularly high alkali resistance and suppressed nonspecific adsorption can be obtained.
[0026] In addition, l, m, and n are based on Fig. 2 and Table 1 in the Journal of the Japan Oil Chemists' Association, Vol. 49, No. 10, 1071, and are calculated by referring to the catalog values of each company, for example, (C 2 H 4 O) part, (C 3 H 8 O) The l, m, and n values can be calculated from the weight of the portion.
[0027] Examples of such block copolymers that can be used include the Pluronic (registered trademark) L, P, and F series manufactured by ADEKA Corporation and BASF. Of these, L35, F38, L42, L43, L44, L62, L63, L64, L72, P65, F68, P75, F77, P84, P85, F87, F88, L92, P94, F98, P103, P104, P105, F108, L122, P123, and F127 can be used.
[0028] (Characteristics of filler) A schematic structure of the filler of this embodiment is shown below, for example.
[0029] [ka] The average particle size of the packing material is not particularly limited as long as it is 10 μm or more, but it is preferably in the range of 15 to 100 μm from the viewpoint of column packing properties and the like. Here, the average particle size is expressed as a volume-converted average particle size. The volume-converted average particle size is a value obtained by an image analysis type particle size distribution measuring device. When an image analysis type particle size distribution measuring device is used for the volume-converted average particle size, the circle-equivalent diameter (diameter of a circle having the same area as the projected area of the particle image) of each particle is obtained from a two-dimensional particle image (preferably a still image) obtained by photographing 2000 or more crosslinked polymer particles with an image analysis type particle size distribution measuring device, and the volume of each particle is calculated from the circle-equivalent diameter, and the particle size is averaged based on the volume. At this time, each particle is regarded as a sphere having the same diameter as the circle-equivalent diameter. As the image analysis type particle size distribution measuring device, for example, a flow type particle image analyzer (product name: FPIA-3000, manufactured by Sysmex Corporation) can be used. The average particle size of the packing material can be adjusted by the polymerization conditions during the production of the carrier.
[0030] The packing material of this embodiment preferably has an exclusion limit molecular weight of 1,000,000 or more. The exclusion limit molecular weight is adjusted by the size of the pores of the packing material. The exclusion limit molecular weight can be determined by a commonly known method in which a column packed with the packing material is connected to a high performance liquid chromatograph, standard substances of various molecular weights are injected into the column at a flow rate of 1.0 mL per minute using ion-exchanged water as the mobile phase, and the elution volume is used. In this embodiment, a differential refractive index detector (product name: RI-201H, manufactured by Showa Denko K.K.) is used for detection, and a pullulan standard (product name: Shodex (registered trademark) STANDARD P-82, manufactured by Showa Denko K.K.) is used as the standard substance.
[0031] In order to separate large proteins by size exclusion chromatography, it is preferable that the exclusion limit molecular weight is 1 million or more. For example, when separating large proteins such as IgM with a molecular weight of about 900,000 and IgG with a molecular weight of about 150,000, if the exclusion limit is less than 1 million, IgM will fall into the exclusion limit region and separation will be impossible.
[0032] The exclusion limit molecular weight can be adjusted by the type and amount of the diluent used during production, or the ratio of glycidyl methacrylate and the polyfunctional monomer, as described below. The average particle size and pore size of the filler do not vary depending on the surface structure. (Filler manufacturing method) The method for producing the filler of this embodiment includes the steps of: A step of polymerizing raw material monomers including glycidyl methacrylate and a polyfunctional monomer in the presence of a diluent and a polymerization initiator to obtain a porous organic polymer carrier α, A step (A) of adjusting the concentration of the polyfunctional monomer in the raw material monomer to 5 mol % to 40 mol % and using the diluent in an amount of 0.8 to 4.0 times the volume of the raw material monomer; and (B) a step of ring-opening the glycidyl group derived from the glycidyl methacrylate of the porous organic polymer carrier α with a block copolymer represented by formula 1 to obtain a filler β in which one end of the block copolymer represented by formula 1 is bonded to the porous organic polymer carrier α via an ether bond derived from a terminal hydroxyl group. [Process (A)] A porous organic polymer carrier α is prepared from a copolymer having glycidyl methacrylate and polyfunctional monomer units. The porous organic polymer carrier α is obtained by copolymerizing these monomers in the presence of a diluent and a polymerization initiator. These porous particles can be produced by referring to the methods described in JP-A-2007-170907, WO2006 / 132333, etc.
[0033] The concentration of the glycidyl methacrylate in the raw material monomer is 60 to 95 mol%, preferably 70 to 95 mol%, and the concentration of the polyfunctional monomer in the raw material monomer is 5 mol% to 40 mol%, preferably 5 mol% to 30 mol%.
[0034] As described above, the polymer may also contain other monomer components.
[0035] In order to introduce pores into the porous organic polymer carrier α, in step (A), a diluent is added to the monomer mixture and polymerized. The diluent is an organic solvent that dissolves in the monomer mixture but is inactive in the polymerization reaction and does not dissolve the copolymer produced. After polymerization is complete, the diluent is removed by washing or other methods, making the diluent portion hollow and forming porous pores in the porous organic polymer carrier α.
[0036] The amount of diluent added affects the exclusion limit molecular weight of the filler and the volume percentage of the pore volume (which indicates the ratio of the pore volume to the total volume of the filler particles). Therefore, the amount is appropriately adjusted before addition. The amount of these diluents added is 0.8 to 4.0 times, preferably 1.0 to 3.0 times the total volume of the raw material monomers at the charging temperature.
[0037] Examples of the diluent that can be used include aromatic hydrocarbons such as toluene, xylene, diethylbenzene, dodecylbenzene, and chlorobenzene; saturated hydrocarbons such as hexane, heptane, pentane, octane, nonane, and decane; alcohols such as isoamyl alcohol, hexyl alcohol, heptyl alcohol, octyl alcohol, and nonyl alcohol; aliphatic halogenated hydrocarbons such as dichloromethane, dichloroethane, and trichloroethane; and aliphatic or aromatic esters such as ethyl acetate, propyl acetate, butyl acetate, pentyl acetate, diethyl succinate, methyl benzoate, ethyl benzoate, and propyl benzoate. These diluents can be used alone or in combination of two or more.
[0038] The polymerization initiator used during polymerization is not particularly limited as long as it is a known radical polymerization initiator that generates radicals, but examples include azo-based initiators such as 2,2'-azobisisobutyronitrile, 2,2'-azobis(methyl isobutyrate), and 2,2'-azobis(2,4-dimethylvaleronitrile). Of these, it is preferable to use 2,2'-azobis(2,4-dimethylvaleronitrile) because of the affinity of the chemical structure. There is no particular limitation on the concentration of the polymerization initiator, but it is preferably 0.1 to 5 parts by mass relative to 100 parts by mass of the total amount of monomers.
[0039] An oil phase containing raw monomers is prepared from a mixture of raw monomers, a diluent, and a polymerization initiator. The oil phase is stirred and suspended in an aqueous medium containing an appropriate dispersion stabilizer to form oil droplets. By polymerizing in this state (suspension polymerization), a copolymer is produced as porous particles with an appropriate particle size. In addition to the above-mentioned stirring method, the oil droplets can be produced by dropping a monomer solvent containing a diluent into an aqueous medium through a porous membrane or a microchannel formed on a quartz substrate.
[0040] As the dispersion stabilizer contained in the aqueous medium, a known one can be used. Usually, a water-soluble polymer compound such as gelatin, sodium polyacrylate, polyvinyl alcohol, etc. is used. In general, polyvinyl alcohol is used. The concentration of the dispersion stabilizer is preferably 0.1 to 5% by mass relative to the aqueous medium.
[0041] The aqueous medium may contain salts and other water-soluble components in addition to water. Examples of salts include commonly used salts such as sodium chloride and calcium chloride. Since the solubility varies depending on the salt used, the concentration cannot be generally specified, but for example, sodium chloride can be dissolved at 0.1 to 15 mass %, and calcium chloride can be dissolved at 1 to 40 mass %. The salts are added for salting out.
[0042] After nitrogen gas replacement, the suspension polymerization reaction is usually heated to 40 to 100°C under stirring and reacted at atmospheric pressure for 5 to 16 hours. At this time, the monomers contained in each oil droplet are polymerized in a state containing a diluent, and a polymer grows in a network shape, so that porous particles can be obtained by removing the diluent later. After the reaction, the porous particles can be easily separated from the aqueous medium by filtration or the like. Furthermore, the porous particles are washed with a solvent such as acetone, methanol, or diethylene glycol dimethyl ether to remove the diluent. After drying, the obtained porous particles having glycidyl groups are classified by a sieve or an air classification device.
[0043] The copolymer thus obtained in step (A) is a porous organic polymer particle having glycidyl groups derived from glycidyl methacrylate, and has the average particle size and pores as described above. [Process (B)] Next, the glycidyl group derived from the glycidyl methacrylate of the porous organic polymer carrier α is subjected to a ring-opening reaction with the block copolymer represented by the above formula 1.
[0044] This gives a filler β in which one end of the block copolymer represented by the above formula 1 is bonded to the porous organic polymer carrier α via an ether bond derived from a terminal hydroxyl group.
[0045] As such block copolymers, Pluronic (registered trademark) L, P, and F series manufactured by ADEKA Corporation and BASF Co., Ltd. can be used as described above.
[0046] The ratio of m in the total of l, m and n of the block copolymer, and the total of l, m and n are as described above.
[0047] The amount of the block copolymer used is preferably 100 to 8,000 parts by mass per 100 parts by mass of the porous organic polymer carrier α. If used within this range, it is possible to obtain a packing material that has high alkali resistance and suppresses nonspecific adsorption.
[0048] For the ring-opening reaction, boron trifluoride diethyl ether complex, zinc borofluoride, trimethylsilyl trifluoromethanesulfonic acid, sulfuric acid, trifluoromethanesulfonic acid, trifluoroacetic acid, dichloroacetic acid, etc. can be used as a catalyst. The catalyst is preferably 0.1 to 100 parts by mass, more preferably 0.5 to 20 parts by mass, per 100 parts by mass of the porous organic polymer carrier α. If it is within this range, the block copolymer can be introduced, and the ester group of the porous organic polymer carrier α can be prevented from reacting. The ring-opening reaction is usually carried out in the presence of a solvent. Diethylene glycol dimethyl ether, etc. can be used as the solvent.
[0049] The resulting porous particles into which the block copolymer has been introduced (i.e., filler β) are washed with dimethyl sulfoxide or the like to remove excess block copolymer, catalyst, and the like.
[0050] In addition, the resulting filler β may contain unreacted glycidyl groups, which may increase the hydrophobicity of the filler and may hydrophobically adsorb highly hydrophobic water-soluble compounds such as proteins. Therefore, it is desirable to open the ring of the remaining glycidyl groups with a mineral acid in order to further increase the hydrophilicity.
[0051] Examples of mineral acids include sulfuric acid, nitric acid, and hydrochloric acid. Of these, sulfuric acid is particularly preferred. The concentration of the mineral acid used may be about 0.01M to 1.0M, and is particularly preferably about 0.1 to 0.5M. If the mineral acid is 0.01M or more, ring opening is sufficiently carried out, and if the mineral acid is 1.0M or less, ester groups in the carrier are not hydrolyzed to generate ionic functional groups. The resulting particles can be washed with water to easily remove excess mineral acid.
[0052] The packing material of the present embodiment has suitable hydrophilicity and exclusion limit molecular weight. Therefore, by packing this packing material into a liquid chromatography case, a high-performance size-exclusion chromatography column can be obtained, and further, a chromatography device equipped with this size-exclusion chromatography column can be obtained. In addition, by using this size-exclusion chromatography column, a method for separating and separating biopolymers can be provided, which can accurately separate and further separate biopolymers with an aqueous eluent.
[0053] In addition, since the filler has high alkali resistance, it can be washed and reused, allowing for long-term continuous use. EXAMPLES
[0054] The effects of the present invention will be more clearly understood by the following examples. Note that the present invention is not limited to the following examples, and can be modified as appropriate without departing from the spirit and scope of the present invention. [Example 1] <Porous organic polymer support α: synthesis of copolymers having glycidyl groups> In 47.0 g of butyl acetate as a diluent, 33.2 g of glycidyl methacrylate (product name: Blenmer G (registered trademark), manufactured by NOF Corporation), 5.9 g of ethylene glycol dimethacrylate (product name: NK Ester 1G, manufactured by Shin-Nakamura Chemical Co., Ltd.), 11.7 g of chlorobenzene, and 1.9 g of 2,2'-azobis(2,4-dimethylvaleronitrile) were dissolved, and nitrogen gas was bubbled through the solution for 30 minutes to prepare an oil phase.
[0055] Next, separate from the oil phase, an aqueous phase was prepared by dissolving 10.0 g of a dispersion stabilizer, PVA-224 (polyvinyl alcohol with a saponification degree of 87.0%-89.0%, manufactured by Kuraray Co., Ltd.), and 10.0 g of a salting-out agent, sodium chloride, in 480 g of water.
[0056] The aqueous phase and the oil phase were transferred to a separable flask and dispersed for 20 minutes at a rotation speed of 430 rpm using a stirring rod equipped with a half-moon stirring blade, after which the inside of the reactor was replaced with nitrogen and reacted at 60°C for 16 hours. The resulting polymer was then transferred onto a glass filter and thoroughly washed in the order of warm water at about 50-80°C, acetone, and water, to obtain 125 g of porous organic polymer carrier α1, which is a porous organic polymer particle. The amount of glycidyl methacrylate used was 88.7 mol% relative to the total amount of monomers, and the amount of ethylene glycol dimethacrylate used was 11.3 mol% relative to the total amount of monomers. <Ring-opening reaction of glycidyl group> 100 g of the porous organic polymer carrier α1 was weighed out on a glass filter and thoroughly washed with diethylene glycol dimethyl ether. After washing, the porous organic polymer carrier α1 was transferred to a separable flask, and 400 g of diethylene glycol dimethyl ether, HO-(C 2 H 4 O) l -(C 3 H 6 O) m -(C 2 H 4 O) n 400 g of a block copolymer represented by -H (ADEKA Corporation, ADEKA Pluronic (registered trademark) L35, l is 11, m is 16, n is 11, l + m + n is 38, m / (l + m + n) is 43%) was transferred to a 1 L separable flask and stirred and dispersed. Then, 2.0 ml of boron trifluoride diethyl ether complex was added, and the temperature was raised to 80 ° C. while stirring at 200 rpm, and the reaction was carried out for 4 hours, and the glycidyl group was opened, and a packing material β1 in which one end of the block copolymer was bonded to the porous organic polymer carrier α1 via an ether bond derived from the terminal hydroxyl group was obtained. After cooling, the obtained packing material β1 was filtered and thoroughly washed with water, and 138 g of packing material β1 was obtained.
[0057] The progress of the ring-opening reaction was confirmed by the following procedure. A part of the filler β1 into which the block copolymer was introduced was mixed with potassium bromide, and pelletized under pressure. The pellet was then measured by FT-IR (product name: Nicolet (registered trademark) iS10, manufactured by Thermo Scientific Co., Ltd.). The infrared absorption spectrum showed a 908 cm -1 The absorbance peak height of 908 cm was confirmed by FT-IR. -1 No absorbance peak was observed.
[0058] The resulting filler β1 was classified using a sieve into particles having a particle size range of 16 to 37 μm, to obtain 117.3 g of filler β1. <Alkaline resistance evaluation> The alkali resistance was evaluated by calculating the amount of carboxyl groups produced by hydrolysis of sodium hydroxide according to the following procedure.
[0059] First, 4 g of the packing material was dispersed in 150 mL of 0.5 mol / L potassium chloride aqueous solution, and titrated with 0.1 mol / L sodium hydroxide aqueous solution at the neutralization point of pH 7.0. From this, the amount of carboxyl groups contained in the packing material before hydrolysis was calculated using the following formula.
[0060] Amount of carboxyl group (μmol / mL) = 0.1 × volume of sodium hydroxide solution at neutralization point (μL) / apparent volume of packing material (mL) Here, the apparent volume of the filler is the volume measured after dispersing 4 g of the filler in water to prepare a slurry, transferring the slurry to a measuring cylinder, and leaving it to stand for a sufficient period of time.
[0061] Next, 4 g of the packing material was weighed into a separable flask, 20 mL of 5 mol / L aqueous sodium hydroxide was added, and the hydrolysis reaction was carried out at 50°C for 20 hours while stirring at 200 rpm. After cooling, the packing material treated with sodium hydroxide was filtered, washed with 0.1 mol / L aqueous HCl solution and water in that order, and the amount of carboxyl groups contained in the obtained packing material was calculated using the same method as above. The amount of carboxyl groups generated by the reaction with 5 mol / L aqueous sodium hydroxide was calculated from the difference in the amount of carboxyl groups before and after the reaction with 5 mol / L aqueous sodium hydroxide. As a result, the amount of carboxyl groups generated was 24.0 μmol / mL.
[0062] If the amount of carboxyl group produced is 40 μmol / mL or less, the alkali resistance is evaluated as being high. <Non-specific adsorption evaluation> The resulting packing material was packed into a stainless steel column (manufactured by Sugiyama Shoji Co., Ltd.) having an inner diameter of 8 mm and a length of 300 mm by the equilibrium slurry method. A non-specific adsorption test was carried out using the resulting column by the method described below.
[0063] The column packed with the packing material was connected to a Shimadzu HPLC system (a liquid delivery pump (product name: LC-10AT, manufactured by Shimadzu Corporation), an autosampler (product name: SIL-10AF, manufactured by Shimadzu Corporation), and a photodiode array detector (product name: SPD-M10A, manufactured by Shimadzu Corporation)), and 50 mmol / L sodium phosphate buffer was passed through the column as the mobile phase at a flow rate of 0.6 mL / min. Using the same sodium phosphate aqueous solution as the mobile phase, 0.7 mg / mL thyroglobulin (Mw 6.7 × 10 5 ), 0.6 mg / mL γ-globurin (Mw1.6×10 5 ), 0.96mg / mL BSA (Mw6.65×10 4 ), 0.7 mg / mL ribonuclease (Mw 1.3 × 10 4 ), 0.4mg / mL Aprotinin (Mw6.5×10 3), and 0.02 mg / mL uridine (Mw 244) (all from Merck Sigma-Aldrich) sample solutions were prepared, and 10 μL of each was injected from the autosampler. The elution times of each sample observed using a photodiode array detector with a wavelength of 280 nm were compared, and it was confirmed that there was no inconsistency between the order of elution volume and the order of molecular weight. If there was no inconsistency between the order of molecular weight and elution volume of the samples, there was no nonspecific adsorption, and this was indicated as 〇 in Table 1. If there was an inconsistency, nonspecific adsorption was induced, and this was indicated as ×.
[0064] As a result, the elution volumes of each sample from the column packed with packing material β1 were 11.437 mL, 11.841 mL, 11.883 mL, 12.094 mL, 12.262 mL, and 12.986 mL, confirming that there was no inconsistency between the molecular weight of the samples and the elution volume order and that nonspecific adsorption was not induced. [Example 2] In the ring-opening reaction of the glycidyl group, HO-(C 2 H 4 O) l -(C 3 H 6 O) m -(C 2 H 4 O) n Filler β2 was obtained in the same manner as in Example 1, except that 400 g of Adeka Pluronic (registered trademark) L44 (l is 10, m is 23, n is 10, l+m+n is calculated to be 43, and m / (l+m+n) is calculated to be 53%) was used as the block copolymer represented by -H.
[0065] The alkali resistance of the resulting packing material β2 was evaluated in the same manner as in Example 1. As a result, the amount of carboxyl groups produced was 23.2 μmol / mL, confirming that the packing material β2 had excellent alkali resistance.
[0066] Furthermore, the non-specific adsorption evaluation of the obtained packing material β2 was performed in the same manner as in Example 1. As a result, the elution volumes of the respective samples were 11.188 mL, 11.570 mL, 11.687 mL, 11.906 mL, 12.077 mL, and 13.310 mL, and it was confirmed that there was no contradiction between the molecular weight of the sample and the elution volume, and that non-specific adsorption was not induced. [Example 3] During the ring-opening reaction of the glycidyl group, HO-(C 2 H 4 O) l -(C 3 H 6 O) m -(C 2 H 4 O) n Filler β3 was obtained in the same manner as in Example 1, except that 400 g of Adeka Pluronic (registered trademark) P123 (l is 20, m is 69, n is 20, l+m+n is 109, and m / (l+m+n) is 64%) was used as the block copolymer represented by -H.
[0067] The alkali resistance of the resulting packing material β3 was evaluated in the same manner as in Example 1. As a result, the amount of carboxyl groups produced was 22.3 μmol / mL, confirming that the packing material β3 has excellent alkali resistance.
[0068] Furthermore, the non-specific adsorption evaluation of the obtained packing material β3 was performed in the same manner as in Example 1. As a result, the elution volumes of the respective samples were 11.345 mL, 11.671 mL, 11.770 mL, 12.044 mL, 12.160 mL, and 13.235 mL, and it was confirmed that there was no contradiction between the molecular weight of the sample and the elution volume, and that non-specific adsorption was not induced. [Example 4] During the ring-opening reaction of the glycidyl group, HO-(C 2 H 4 O) l -(C 3 H 6 O) m -(C 2 H 4O) n Filler β4 was obtained in the same manner as in Example 1, except that 800 g of a block copolymer represented by -H (ADECA PLURONIC (registered trademark) F68 (l is 76, m is 29, n is 76, l+m+n is 182, and m / (l+m+n) is 16%) was used.
[0069] The alkali resistance of the resulting packing material β4 was evaluated in the same manner as in Example 1. As a result, the amount of carboxyl groups produced was 27.6 μmol / mL, confirming that the packing material β4 has excellent alkali resistance.
[0070] Furthermore, the non-specific adsorption evaluation of the obtained packing material β4 was performed in the same manner as in Example 1. As a result, the elution volumes of the respective samples were 10.71 mL, 11.089 mL, 11.240 mL, 11.584 mL, 11.840 mL, and 13.249 mL, and it was confirmed that there was no contradiction between the molecular weight of the samples and the elution volume, and that non-specific adsorption was not induced. [Example 5] Filler β5 was obtained in the same manner as in Example 3, except that 21.5 g of glycidyl methacrylate (trade name: Blenmer G (registered trademark) manufactured by NOF Corp.), 17.6 g of ethylene glycol dimethacrylate (trade name: NK Ester 1G, Shin-Nakamura Chemical Co., Ltd.), 47.0 g of butyl acetate, 11.7 g of chlorobenzene, and 1.9 g of 2,2'-azobis (2,4-dimethylvaleronitrile) were used as the oil phase, and porous organic polymer carrier α5 synthesized in the same manner as in Example 1 was used. The amount of glycidyl methacrylate used was 63.0 mol% relative to the total amount of monomers, and the amount of ethylene glycol dimethacrylate used was 37.0 mol% relative to the total amount of monomers.
[0071] The alkali resistance of the resulting packing material β5 was evaluated in the same manner as in Example 1. As a result, the amount of carboxyl groups produced was 19.3 μmol / mL, confirming that the packing material β5 has excellent alkali resistance.
[0072] Furthermore, the non-specific adsorption evaluation of the obtained packing material β5 was performed in the same manner as in Example 1. As a result, the elution volumes of the respective samples were 11.387 mL, 11.734 mL, 11.775 mL, 12.043 mL, 12.44 mL, and 12.945 mL, and it was confirmed that there was no contradiction between the molecular weight of the sample and the elution volume, and that non-specific adsorption was not induced. [Example 6] In preparing the porous organic polymer carrier α, 27.8 g of glycidyl methacrylate (trade name: Blenmer G (registered trademark) manufactured by NOF Corp.), 11.3 g of glycerin-1,3-dimethacrylate (trade name: NK Ester 701, manufactured by Shin-Nakamura Chemical Co., Ltd.), 58.7 g of diethyl succinate, and 1.9 g of 2,2'-azobis (2,4-dimethylvaleronitrile) were used as the oil phase, but the same procedure as in Example 1 was used to obtain a filler β6. The amount of glycidyl methacrylate used was 79.8 mol% relative to the total amount of monomers, and the amount of glycerin-1,3-dimethacrylate used was 20.2 mol% relative to the total amount of monomers.
[0073] The alkali resistance of the resulting packing material β6 was evaluated in the same manner as in Example 1. As a result, the amount of carboxyl groups produced was 25.0 μmol / mL, confirming that the packing material β6 has excellent alkali resistance.
[0074] Furthermore, the non-specific adsorption evaluation of the obtained packing material β6 was performed in the same manner as in Example 1. As a result, the elution volumes of the respective samples were 7.58 mL, 8.232 mL, 8.465 mL, 9.075 mL, 9.531 mL, and 12.011 mL, and it was confirmed that there was no contradiction between the molecular weight of the samples and the elution volume, and that non-specific adsorption was not induced. [Comparative Example 1] The ring-opening reaction of the glycidyl group is 2 H 4 O) l -(C 3 H 6 O) m -(C 2 H 4 O) nFiller β7 was obtained in the same manner as in Example 1, except that 400 g of a block copolymer represented by -H (Pluronic (registered trademark) L121 (l is 5, m is 68, n is 5, l+m+n is 78, and m / (l+m+n) is 87%), manufactured by BASF) was used.
[0075] The non-specific adsorption evaluation of the obtained packing material β7 was carried out in the same manner as in Example 1. As a result, the elution volumes of the respective samples were 11.557 mL, 11.584 mL, 11.585 mL, 11.866 mL, 14.750 mL, and 12.487 mL, and it was confirmed that there was a discrepancy between the molecular weight of the sample and the elution volume, and that non-specific adsorption was induced.
[0076] The alkali resistance of the resulting packing material β7 was evaluated in the same manner as in Example 1. As a result, the amount of carboxyl groups produced was 11.2 μmol / mL. [Comparative Example 2] Filler β8 was obtained in the same manner as in Example 1, except that 400 g of PEG2000 (manufactured by Kanto Chemical Co., Ltd., average molecular weight 1900 to 2100) was used as polyethylene glycol in the ring-opening reaction of the glycidyl group. 3 H 6 O) m -There is no equivalent block structure.
[0077] The non-specific adsorption evaluation of the obtained packing material β8 was carried out in the same manner as in Example 1. As a result, the elution volumes of the respective samples were 11.1702 mL, 11.5425 mL, 11.6449 mL, 11.9073 mL, 12.0849 mL, and 13.1952 mL, and it was confirmed that there was no inconsistency between the molecular weight of the samples and the elution volume, and that non-specific adsorption was not induced.
[0078] The alkali resistance of the resulting packing material β8 was evaluated in the same manner as in Example 1. As a result, the amount of carboxyl groups generated in the packing material β8 was 148.3 μmol / mL. [Comparative Example 3] In preparing the polymer α having a glycidyl group, 37.1 g of glycidyl methacrylate (trade name: Blenmer G (registered trademark) manufactured by NOF Corp.), 2.0 g of ethylene glycol dimethacrylate (trade name: NK Ester 1G, Shin-Nakamura Chemical Co., Ltd.), 47.0 g of butyl acetate, 11.7 g of chlorobenzene, and 1.9 g of 2,2'-azobis (2,4-dimethylvaleronitrile) were used as the oil phase, but the procedure was the same as in Example 1 to obtain a filler β9. The amount of glycidyl methacrylate used was 96.3 mol% relative to the total amount of monomers, and the amount of ethylene glycol dimethacrylate used was 3.7 mol% relative to the total amount of monomers.
[0079] The alkali resistance of the obtained packing material β9 was evaluated in the same manner as in Example 1. As a result, the amount of carboxyl group generated was 20.5 μmol / mL. An attempt was made to pack the obtained packing material β9 into a stainless steel column. However, the back pressure was high, making it difficult to send the liquid, and packing could not be performed. For this reason, non-specific adsorption could not be evaluated. [Comparative Example 4] Filler β10 was obtained in the same manner as in Example 1, except that 13.7 g of glycidyl methacrylate (trade name: Blenmer G (registered trademark) manufactured by NOF Corp.), 25.4 g of ethylene glycol dimethacrylate (trade name: NK Ester 1G, manufactured by Shin-Nakamura Chemical Co., Ltd.), 47.0 g of butyl acetate, 11.7 g of chlorobenzene, and 1.9 g of 2,2'-azobis(2,4-dimethylvaleronitrile) were used in the oil phase. The amount of glycidyl methacrylate used was 42.9 mol% relative to the total amount of monomers, and the amount of ethylene glycol dimethacrylate used was 57.1 mol% relative to the total amount of monomers.
[0080] The alkali resistance of the resulting packing material β10 was evaluated in the same manner as in Example 1. As a result, the amount of carboxyl groups produced was 44.3 μmol / mL.
[0081] The non-specific adsorption evaluation of the obtained packing material β10 was carried out in the same manner as in Example 1. As a result, the elution volumes of the respective samples were 11.437 mL, 12.930 mL, 11.883 mL, 12.094 mL, 13.866 mL, and 12.986 mL, and it was confirmed that there was a discrepancy between the molecular weight of the sample and the elution volume, and that non-specific adsorption was induced.
[0082] It was confirmed that the exclusion limit molecular weight of the packing materials obtained in Examples 1 to 6 and Comparative Examples 1, 2, and 4 was 1 million or more.
[0083] From the above results, by adopting the configuration of the present invention, a packing material with high alkali resistance and suppressed non-specific adsorption can be obtained.
[0084] In Comparative Example 1, in which the ratio of l, m, or n was outside the range of the present invention, nonspecific adsorption was induced, and −(C 3 H 6 O) m Comparative Example 2, which does not contain a block corresponding to -, was found to have low alkali resistance.
[0085] It was found that Comparative Example 3, in which the amount of repeating units derived from the polyfunctional monomer was too small, could not be used due to high back pressure in the size exclusion chromatography column, and Comparative Example 4, in which the amount of repeating units derived from the polyfunctional monomer was too large, induced nonspecific adsorption.
[0086] [Table 1]
Claims
1. A filler having an exclusion limit molecular weight of 1,000,000 or more, comprising a porous organic polymer carrier containing 60 to 95 mol % of repeating units derived from glycidyl methacrylate and 5 to 40 mol % of repeating units derived from a polyfunctional monomer, and one end of a block copolymer represented by the following formula 1 being bonded via an ether bond derived from a terminal hydroxyl group. (Formula 1) HO-(C 2 H 4 O) l -(C 3 H 6 O) m -(C 2 H 4 O) n -H (In formula 1, l is an integer from 5 to 140, m is an integer from 15 to 75, and n is an integer from 5 to 140. The proportion of m in the total of l, m, and n is 5 to 85%.)
2. 2. The filler according to claim 1, wherein the sum of l, m, and n of the block copolymer is 30 to 330.
3. The filler of claim 1 , wherein the multifunctional monomer is a (meth)acryloyl-based monomer containing two or more (meth)acryloyl groups.
4. 4. The filler according to claim 3, wherein the polyfunctional monomer is either ethylene glycol dimethacrylate or glycerin-1,3-dimethacrylate.
5. A step of polymerizing raw material monomers including glycidyl methacrylate and a polyfunctional monomer in the presence of a diluent and a polymerization initiator to obtain a porous organic polymer carrier α, A step (A) of adjusting the concentration of the polyfunctional monomer in the raw material monomer to 5 mol % to 40 mol % and using the diluent in an amount of 0.8 to 4.0 times the total volume of the raw material monomer; and (B) a step of ring-opening a glycidyl group derived from glycidyl methacrylate of the porous organic polymer carrier α with a block copolymer represented by formula 1 to obtain a filler β in which one end of the block copolymer represented by formula 1 is bonded to the porous organic polymer carrier α via an ether bond derived from a terminal hydroxyl group. (Formula 1) HO-(C 2 H 4 O) l -(C 3 H 6 O) m -(C 2 H 4 O) n -H (In formula 1, l is an integer from 5 to 140, m is an integer from 15 to 75, and n is an integer from 5 to 140. The proportion of m in the total of l, m, and n is 5 to 85%.)
6. A size exclusion chromatography column comprising a liquid chromatography case packed with the packing material according to any one of claims 1 to 4.
Citation Information
Patent Citations
Method of making resinoid grinding stone
JP1978015691A
Granular adsorbent and manufacture thereof
JP1988287550A
Hydrophobic polymer particle, method for producing the same, and column for reversed-phase high-speed liquid chromatography
JP2003176363A
METHOD FOR SELECTIVE REMOVAL OF SUBSTANCE FROM SAMPLE CONTAINING COMPOUND HAVING NUCLEIC ACID STRUCTURE
JP2003514655A
Photosensitive composition
JP2005194476A